2002
DOI: 10.1007/bf03179844
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del ayuno y del precondicionamiento hipóxico en bandas de ventrículo del corazón de rata expuestas a hipoxia-reoxigenación

Abstract: The investigation aimed to assess the effects of hypoxic preconditioning in right ventricle strips of fed and 24-h fasted rats, which display a fast fatty acid catabolism, and to ascertain whether these effects are associated with changes in the tissue levels of long-chain acylCoA and acyl carnitine and glycolytic activity. Strips were mounted isometrically in Krebs-bicarbonate solution with 10 mM dextrose and paced at 1 Hz. Strips were exposed to 30 min hypoxia and 60 min reoxygenation with or without a previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In agreement with previous studies hypoxic preconditioning (10 min hypoxia followed by 20 min reoxygenation) significantly enhanced contractile recovery seen after 30 min hypoxia followed by reoxygenation for 30 min (see Fig. 2; Cerruti et al 2002). Similarly, application of 10 μ m adenosine 2 min before exposure to hypoxia (30 min) significantly improved posthypoxia contraction (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies hypoxic preconditioning (10 min hypoxia followed by 20 min reoxygenation) significantly enhanced contractile recovery seen after 30 min hypoxia followed by reoxygenation for 30 min (see Fig. 2; Cerruti et al 2002). Similarly, application of 10 μ m adenosine 2 min before exposure to hypoxia (30 min) significantly improved posthypoxia contraction (Fig.…”
Section: Resultssupporting
confidence: 93%
“…In this study, we have investigated the possible involvement of ERK1/2 and PI3‐kinase in adenosine receptor‐induced preconditioning using rat ventricle strips. Previous studies have used rat right ventricle strips as a model system for studying ischaemic preconditioning (Cerruti et al 2002) and pharmacological preconditioning triggered by adenosine, phenylephrine and atrial natriuretic peptide (Cleveland et al 1996; Ljusegren & Andersson, 1994). In agreement with these previous studies both hypoxic preconditioning and adenosine (10 μ m ) improved posthypoxic contraction compared to control ventricle strips exposed to 30 min hypoxia alone.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence of cardioprotection on the number of HPC cycles has been confirmed by others. In isolated rat hearts Testoni et al (2000) and later Cerruti et al (2002), showed that as long as the animals were exposed only to hypoxia (60 min.) and reoxygenation (60 min.…”
Section: Ventricular Arrhythmia Threshold -A Measure Of the Electricamentioning
confidence: 99%
“…The differences in the number of cycles of hypoxia necessary for the mobilization of the cardioprotective mechanism in the prezent study and previous studies performed in vitro and in vivo, could be explained by different experimental procedures. Low-oxygen perfusion of isolated hearts in vitro (Testoni et al, 2000;Cerruti et al, 2002) may facilitate cardioprotection much sooner compared to an in vivo condition. The anaesthesia in in vivo experiments is an important variable, as is the animal species in use, e.g., ketamine anaesthesia inhibits PC with anoxia in rats (Ko et al, 1997), in rabbits (Han et al, 2002), and in our results, or -chloralose in beagles (O'Connor & Merrill, 1993).…”
Section: Ventricular Arrhythmia Threshold -A Measure Of the Electricamentioning
confidence: 99%
“…[67][68][69][70][71][72]. Long-chain fatty acids released during ischemia may contribute to tissue injury [73][74][75][76][77][78][79][80]. In particular, they increase the open probability of sarcolemmal or intracellular Ca 2+ channels, by acting directly on the channel protein or by modifying the protein/lipid interface, contributing to cytotoxic Ca 2+ overload (See Section 3.3) [81].…”
Section: Toxic Lipid Metabolitesmentioning
confidence: 99%